Prognosis of obstructive nephropathy patients after percutaneous nephrostomy - Sukmagara, Jefri; Danarto, H R (Indonesian Journal of Urology, 2015)
Background: Percutaneous nephrostomy is a life-saving procedure for the treatment of obstructive uropathy associated with septicaemia and uraemia. It is regarded as a temporary interventional procedure before definitive treatment. Several factors can affect recovery of renal function after nephrostomy, such as patient age, duration of obstruction, function of the contralateral kidney, pyelolymphatic backflow and compliance of the ureter and renal pelvis.Objective: To determine factors that can predict the decrease in creatinine levels after percutaneous nephrostomy (< 2mg/dl).Methods: This is a retrospective analysis descriptive study. All patients previously performed nephrostomy at Sardjito General Hospital Yogyakarta, from January 2009 to December 2012 were identified. The data were analyzed to evaluate the relationship between reduction of serum creatinine level and following variables including: etiology, nephrostomy (unilateral or bilateral), symptom duration (≤14 days or >14 days), comorbid disease (hypertension, diabetes melitus, heart disease) and degree of hydronephrosis (mild, moderate and severe). The data were analyzed with Chi-Square test and multiple logistic regression to obtain predictive factor and predictive scoring equation to measure the possibility of recoverability of renal function after nephrostomy.Results: We analyzed 117 patients that previously treated by percutaneous nephrostomy. It showed the relationship between reduction of serum creatinine level and the following variables:  nephrostomy (unilateral or bilateral) (p=0,000), symptom duration (p=0,000), hypertension (p=0,004) and degree of hydronephrosis (p=0,000). Whereas etiology of urinary obstruction and other comorbid diseases showed no relationship. Predictive equation result: P= 1/(1+ey), where y= -0,271 + 1,636 (degree of hydronephrosis) + ((-2,216) unilateral or bilateral nephrostomy) + 1,694 (symptom duration) + ((-0,862) hypertension), with sensitivity 74,3% and specificity 70,7% in predicting renal function recoverability.Conclusions: Bilateral or unilateral nephrostomy, symptom duration, hypertension and degree of hydronephrosis are factors affecting the decrease in serum creatinine level. They role as independent predictor to predict recoverability of renal function can be considered. Key words: obstructive uropathy, percutaneous nephrostomy, multiple logistic regression.